2009
DOI: 10.1002/joc.2036
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land cover data quality on regional climate simulations

Abstract: ABSTRACT:The land surface influences local, regional and global climate across many time scales. Accurate representation of land surfaces is an important factor for climate modelling studies because land surfaces control the partitioning of available energy and water. Here we introduce new, up-to-date and accurate land cover data for the Marmara Region, Turkey derived from Landsat Enhanced Thematic Mapper (ETM+) images into the Weather Research and Forecasting (WRF) model. We used several image processing tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 26 publications
5
86
0
Order By: Relevance
“…Because of the importance of land surface processes in regional dynamic downscaling, a number of studies have investigated the impact of specification of initial soil moisture and land conditions from data assimilation systems and satellite products (e.g., Pielke et al, 1997;Hong et al, 2009;Moufouma-Okia and Rowell, 2010;Sertel et al, 2010;Panegrossi et al, 2011). Using high resolution soil moisture data derived from ENVISAT/ASAR observations as the initial conditions for the MM5 simulation of the Tanaro flood event of April 2009, the ASAR-derived soil moisture field shows significantly drier conditions compared to the ECMWF analysis and significantly improved the simulation in timing of the onset of the precipitation, as well as the intensity of rainfall and the location of rain/no rain areas (Panegrossi et al, 2011).…”
Section: Specification Of Initial Soil Moisture and Vegetation Conditmentioning
confidence: 99%
“…Because of the importance of land surface processes in regional dynamic downscaling, a number of studies have investigated the impact of specification of initial soil moisture and land conditions from data assimilation systems and satellite products (e.g., Pielke et al, 1997;Hong et al, 2009;Moufouma-Okia and Rowell, 2010;Sertel et al, 2010;Panegrossi et al, 2011). Using high resolution soil moisture data derived from ENVISAT/ASAR observations as the initial conditions for the MM5 simulation of the Tanaro flood event of April 2009, the ASAR-derived soil moisture field shows significantly drier conditions compared to the ECMWF analysis and significantly improved the simulation in timing of the onset of the precipitation, as well as the intensity of rainfall and the location of rain/no rain areas (Panegrossi et al, 2011).…”
Section: Specification Of Initial Soil Moisture and Vegetation Conditmentioning
confidence: 99%
“…Most of the studies examine regional impacts of land surface states on climate (Costa and Pires, 2010;Fall et al, 2010aFall et al, , 2010bGe, 2010;Kishtawal et al, 2010;Mishra et al, 2010;Moore et al, 2010;Petchprayoon et al, 2010;Sertel et al, 2010;Takahashi et al, 2010;Tokairin et al, 2010;Xiao et al, 2010). However, several studies take a global perspective of land-cover consequences Kvalevåg et al, 2010;Lawrence and Chase, 2010;Strengers et al, 2010).…”
Section: Impacts Of Land Use Change On Climatementioning
confidence: 99%
“…The observational studies use in situ climate data (Petchprayoon et al, 2010;Xiao et al, 2010), satellite measurements (Ge, 2010;Kishtawal et al, 2010) and data from regional reanalyses (Fall et al, 2010a(Fall et al, , 2010b. The modelling studies use regional atmospheric models (Moore et al, 2010;Sertel et al, 2010;Takahashi et al, 2010;Tokairin et al, 2010;Xiao et al, 2010), global climate models Costa and Pires, 2010;Kvalevåg et al, 2010;Lawrence and Chase, 2010;Strengers et al, 2010) and one uses a land surface model run offline (Mishra et al, 2010).…”
Section: Impacts Of Land Use Change On Climatementioning
confidence: 99%
“…Ge et al (2007) reported that input land cover data with accuracies lower than 80% would have strong impacts on RAMS precipitation simulation in East Africa. Sertel et al (2010) replaced the default Global Land Cover Characteristics dataset in the WRF model with a newly developed land cover map from recent Landsat ETM+ and achieved better temperature simulations for Northwest Turkey. MCD12Q1 products are used widely as input for climate models, but data quality is rarely fully considered.…”
Section: Introductionmentioning
confidence: 99%